Mathematical Problem-Solving Skills in Solving PISA Model Questions on Space Content for Prospective Teacher Students - Muhammad Mahendra Kurniawan; Dede Suratman; Revi Lestari Pasaribu (Postgraduate, University of Mataram, 2025)
This research aims to identify and describe the mathematical problem-solving abilities of prospective mathematics teacher students in solving PISA model questions related to space content at levels 4, 5, and 6. The approach used is a qualitative research approach. The subjects of this study are mathematics education students who are currently enrolled in the Mathematics Education Study Program at Tanjungpura University, classes VA1 and VA2, totaling 19 were test takers and, and 6 of them were interviewed. The data collection tools descriptive tests in the form of PISA model questions related to space content at levels 4, 5, and 6.The data analysis technique employed is Miles and Huberman's data analysis technique, which includes data reduction, data presentation, and conclusion drawing. The research results indicate the mathematical problem-solving ability of prospective mathematics teacher students in solving PISA model questions in the space content at levels 4, 5, and 6 achieved an overall percentage of 61.99% in the medium category. The achievement percentages at levels 4, 5, and 6 were 82.89% in the high category, 65.35% in the medium category, and 37.72% Students needs to be an adaptation in solving PISA by using good and systematic mathematical problem-solving stages.